Back‐contacted back‐junction n‐type silicon solar cells featuring an insulating thin film for decoupling charge carrier collection and metallization geometry. (27th March 2012) - Reichel, Christian; Granek, Filip; Hermle, Martin; Glunz, Stefan W.
ABSTRACT In this study, back‐contacted back‐junction n‐type silicon solar cells featuring a large emitter coverage (point‐like base contacts), a small emitter coverage (point‐like base and emitter contacts), and interdigitated metal fingers have been fabricated and analyzed. For both solar cell designs, a significant reduction of electrical shading losses caused by an increased recombination in the non‐collecting base area on the rear side was obtained. Because the solar cell designs are characterized by an overlap of the B‐doped emitter and the P‐doped base with metal fingers of the other polarity, insulating thin films with excellent electrical insulation properties are required to prevent shunting in these overlapping regions. Thus, with insulating thin films, the geometry of the minority charge carrier collecting emitter diffusion and the geometry of the interdigitated metal fingers can be decoupled. In this regard, plasma‐enhanced chemical vapor deposited SiO2 insulating thin films with various thicknesses and deposited at different temperatures have been investigated in more detail by metal‐insulator‐semiconductor structures. Furthermore, the influence of different metal layers on the insulation properties of the films has been analyzed. It has been found that by applying a SiO2 insulating thin film with a thickness of more than 1000 nm and deposited at 350 °C to solar cells fabricated on 1 Ω cm and 10 Ω cm n‐type float‐zone grown silicon substrates, electrical shading losses could be reduced considerably, resulting in excellent short‐circuit current densities of more than 41 mA/cm2 and conversion efficiencies of up to 23.0%. Copyright © 2012 John Wiley & Sons, Ltd.